MODEL PENINGKATAN KINERJA APIP BERBASIS INTEGRITAS DAN KOMPETENSI YANG DIMEDIASI KOMITMEN ORGANISASI (Studi pada APIP Inspektorat Wilayah Probolinggo) - Mariya Ulfa; Muryati, Muryati; Nasharuddin Mas (Bajang Institute, 2024)
The aim of this research is to obtain empirical evidence of the ability of integrity and competence to encourage improvements in APIP performance, both directly and through the mediation of organizational commitment. Type of research is quantitative with the SEM-SmartPLS method. Data was obtained through a questionnaire distributed to 90 APIPs at the Probolinggo Regional Inspectorate. The sample is determined by census or saturated sample. Empirical evidence shows that both integrity and competence are able to encourage increased APIP performance, both directly and through the mediation of organizational commitment. The mediating role of organizational commitment is quite strong